ANALISA EFEKTIVITAS TEKNIK PERNAPASAN BUTEYKO UNTUK MENURUNKAN FREKUENSI NAPAS DAN MENINGKATKAN SATURASI OKSIGEN PADA PASIEN DENGAN ASMA DI RUANG INSTALASI GAWAT DARURAT RSUD TARAKAN JAKARTA - Riski Dwiana (2022)
Asthma is an inflammation of the airways that causes narrowing of the airways. In Indonesia 4.5% of the population suffers from asthma, specifically for children and adults. Asthma that is not treated properly will lead to respiratory failure and death. The main treatment for asthma attacks is pharmacological therapy by giving bronchodilators to stimulate the respiratory tract muscles so that bronchodilation occurs. Provision of additional therapy with non-pharmacological therapy buteyko breathing technique aims to determine the effectiveness of therapy in decreasing respiratory rate and increasing oxygen saturation in the emergency room so as to prevent the risk of hyperventilation in asthmatics. Measurement of respiratory rate and oxygen saturation were carried out before and after the intervention was given as an evaluation of the results of therapy. The results obtained after doing therapy for 15 minutes showed a 3-point decrease in respiratory rate and a 1% increase in oxygen saturation after the intervention was carried out. Based on the results obtained, it can be concluded that the administration of Buteyko breathing technique therapy can reduce respiratory rate and increase oxygen saturation in asthmatics.